2020
DOI: 10.3390/nu12071972
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum subsp. longum OLP-01 Supplementation during Endurance Running Training Improves Exercise Performance in Middle- and Long-Distance Runners: A Double-Blind Controlled Trial

Abstract: Bifidobacterium longum subsp. longum Olympic No. 1 (OLP-01) has been shown in previous animal experiments to improve exercise endurance performance, but this effect has not been confirmed in humans, or more particularly, in athletes. Toward this end, the current study combined OLP-01 supplementation with regular exercise training in well-trained middle- and long-distance runners at the National Taiwan Sport University. The study was designed as a double-blind placebo-controlled experiment. Twenty-one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 52 publications
(60 reference statements)
1
49
0
Order By: Relevance
“…The 12-minute Cooper running/walking test is used as an initial simple method to assess aerobic endurance and physical fitness 25 . The time is recorded from the start of the run, and the distance traveled is recorded every 3 minutes (3rd, 6, 9th and 12th minutes), as previous described 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 12-minute Cooper running/walking test is used as an initial simple method to assess aerobic endurance and physical fitness 25 . The time is recorded from the start of the run, and the distance traveled is recorded every 3 minutes (3rd, 6, 9th and 12th minutes), as previous described 26 .…”
Section: Methodsmentioning
confidence: 99%
“…The device can screen frequencies of 1, 5, 50, 260, 500 and 1000 kHz within 60 seconds. After cleaning the palms and soles of the feet, the subject stood vertically on the electrodes of the instrument, holding the sensing handle with both hands and keeping the arms away from the body at a 30° angle, and avoided talking or moving during the measurement 26 . We would measurement about body weight (kg), BMI (kg/cm2), fat mass (%), and lean mass (kg).…”
Section: Methodsmentioning
confidence: 99%
“…Their populations are markedly affected by the daily lifestyle of the host, and any consequent changes can cause sub-health conditions such as atopic dermatitis, obesity, asthma, allergic diseases, inflammatory bowel disease, and oral ulcers. The regular human dosage for daily probiotic consumption is around 1* 10 10 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that B. longum subsp. longum from Olympic weightlifters not only promoted athletic performance and reduced post-exercise fatigue in animal experiments but also improved the exercise endurance performance of professional medium-distance runners [24]. Kefir grains contain lactic acid bacteria, acetic bacteria, and yeasts.…”
Section: Discussionmentioning
confidence: 99%